Dynamic pilot assignment in massive MIMO system based on user classification - Jinyan ZHANG; Feng JIN; Lixin YIN (Dianxin kexue)
Aiming at the problem of pilot contamination in massive MIMO system,a dynamic pilot assignment strategy based on user classification was proposed.The target cell user was divided into the central user and the edge user based on the variance of target cell user signal intensity.The central user used the maximum C/I algorithm to assign pilots to maximize the channel capacity of the central user.The edge user used greedy algorithm to assign pilots to improve the signal to interference and noise ratio of each edge user.Simulation results show that the proposed strategy can improve the channel capacity of the system while improving the signal to interference and noise ratio of the edge user.